Effect of Storage condition and period on seed germination of some leguminous seeds - Modi, Anupama; Kandya, Anand (International Journal of Scientific Research in Biological Sciences, 2018)
If the seeds are not to be used immediately they can be stored for long durations, if optimum suitable conditions of moisture temperature, aeration, light etc. are provided to the seeds. Beyond the atmosphere ic humidity, moisture of the seeds is also an important factor as seeds are normally hygroscopic and loosing or gaining of the moisture content depends upon the equilibrium between the moisture status of both the atmosphere and the seeds. Such moisture level is called the equilibrium moisture content which differs from species to species.